Pengembangan Hortikultura Lahan Kering dan Penerapan Teknologi Budidaya Ramah Lingkungan untuk Meningkatkan Pendapatan Petani Di Desa Sukadana Lombok Utara - Jayaputra Jayaputra; I Komang Damar Jaya; Bambang Budi Santoso (Universitas Mataram, 2022)
One important issue of agricultural development in the dry land area of North Lombok Regency is how to increase the Cropping Index that supported by the availability of sufficient water, especially for the development of horticultural commodities. The increase in the Planting Index is expected to lead to an increase in community welfare, specifically an increase in farmers' incomes. The development of horticulture is intended to provide added value to farmers' income by applying environmentally friendly Good Agricultural Practices with production management in accordance with the conditions of natural resources. One area of dry land that has sufficient potential for horticultural development in North Lombok Regency is Sukadana Village. Problems faced by dry land farmers include the level of knowledge and skills of farmers, especially in the management of horticultural commodities and the relatively low level of farmer participation. To overcome these problems, innovation technology transfer is needed through the development of environmentally friendly horticultural crops by regulating cropping systems and improving cultivation technology to increase farmers' incomes. Counseling and training, as well as demonstration plots for improved cultivation technology and regulation of horticultural cropping patterns were carried out during Mei-November 2022. Community service activities were considered quite successful in terms of the enthusiasm and perseverance of participants in participating in counseling and training, as well as demonstration plots (tomato plants, chili peppers, intercropped chili peppers and sawi/pachoy). The results of the demonstration plot showed a significant increase both in crop productivity and increased income per unit area of arable land. On going assistance from all parties, especially the local government, is expected to sustainably develop horticultural commodities in order to increase the income of dry land farmers.